1990
DOI: 10.1016/0960-0760(90)90433-l
|View full text |Cite
|
Sign up to set email alerts
|

Inhibin immunoreactivity in gonadal and non-gonadal tumors

Abstract: Inhibin immunoreactivity was estimated in a number of gonadal and non-gonadal tumors. Dog Sertoli cell tumors and human granulosa cell and Leydig cell tumors contained high concentrations of inhibin-like material. Levels, comparable with those in normal testes and ovaries were detected in human testicular non-seminomas and in ovarian cystadenomas, thecomas and adenofibromas. No activity was found in human testicular Sertoli/Leydig cell tumors and seminomas and in ovarian adenocarcinomas, teratomas and a dysger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 24 publications
3
16
1
Order By: Relevance
“…The low INH-α concentration in the blood plasma of dogs with a cryptorchid testis is assumed to be a risk factor for the occurrence of SCT. However, it has already been reported that SCT cells produce a large amount of INH [8] and that the blood plasma INH concentration of dogs with SCT is very high [13,25], as found in the present study. Abnormal function of SCT cells is thought to cause markedly high INH-α production.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The low INH-α concentration in the blood plasma of dogs with a cryptorchid testis is assumed to be a risk factor for the occurrence of SCT. However, it has already been reported that SCT cells produce a large amount of INH [8] and that the blood plasma INH concentration of dogs with SCT is very high [13,25], as found in the present study. Abnormal function of SCT cells is thought to cause markedly high INH-α production.…”
Section: Discussionsupporting
confidence: 72%
“…Heat shock protein (HSP) 70 is the main protein produced abundantly in some tissues exposed to heat stress [22], and it induces the development of certain tumors [6,18,20]. Inhibin (INH) in male animals is a glycoprotein produced by Sertoli cells [23,24,28] and is composed of two subunits, an α-unit and a β-unit [8,23]. The bioactivity of INH-α is important for spermatogenesis in the testis [11,24,29] and is especially correlated with Sertoli cell function [19,21].…”
mentioning
confidence: 99%
“…Apparently, this is not a general phenomenon as the other mature teratoma/yolk sac tumour in our panel did not give rise to relatively high expression levels for inhibin a-and fiB subunits; in addition, pure yolk sac or mature teratoma tumours were negative for inhibin a-subunit mRNA. Evidence for inhibin immunoreactivity in homogenates of non-seminomas has been presented earlier (de Jong et al, 1990), indicating that inhibin synthesis can occur in non-seminomas. As n-subunit expression is found in all tumours investigated so far, while inhibin a-subunit is expressed in only a few, one could speculate that a-subunit synthesis occurs at a later stage in the development of some tumours, thereby affecting activin-induced differentiation processes.…”
Section: Inhibin Subunits and Follistatinmentioning
confidence: 83%
“…In mouse embryonal carcinoma cells, activin was shown to act as a growth factor in undifferentiated P19 cells (Hashimoto et al, 1990), while retinoic acid-induced differentiation of these cells could be blocked by activin (Hashimoto et al, 1990;van den Eijnden-van Raaij et al, 1991). Furthermore, inhibin immunoreactivity has been demonstrated in clinical samples of human TGCTs (de Jong et al, 1990). These observations led us to investigate whether clinical germ cell tumours express activin receptors and inhibin/activin subunits.…”
mentioning
confidence: 99%
“…The a-subunit, rather than dimeric forms, seems to be increased in epithelial ovarian carcinomas (Lambert-Messerlian et al, 1997;Ala-Fossi et al, 2000). In human testicular tumors, inhibin b-subunit has been shown to be expressed in germ cell tumors (De Jong et al, 1990). Although the major circulating dimeric form in males in inhibin B (Illingworth et al, 1996), also the role of inhibin A as a tumor marker in males, is supported by studies showing that Leydig cell and testicular sex cord-stromal tumors produce inhibin A (Herath et al, 2001, Iczkowski et al, 1998.…”
Section: Discussionmentioning
confidence: 99%